AN OBSERVATIONAL STUDY OF CESAREAN TRENDS AT A TEACHING HOSPITAL IN PUNJAB - GROVER, SUPARNA; MEENA, SUNITA; CHHABRA, AJAY (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: The objective of the study was to study the indications and risk factors for caesarean section (CS) and to study the caesarean rates in various patient groups as per Robson’s classification. Methods: This prospective observational study was conducted at Government Medical College Amritsar over a period of six months. All the patients admitted for delivery beyond 22 weeks were allotted to Robson groups on admission and the indications of all CS were recorded. The data collected were tabulated and analyzed statistically. Results: There were 553 deliveries in the study period, of which there were 241 CS amounting to a caesarean rate of 43.6%. Nulliparity, previous caesarean delivery and malpresentation were significant risk factors for CS but induction of labor was not associated with increased probability of caesarean delivery. Previous caesarean delivery was the most common indication of CS followed by foetal distress. Among Robson groups, group 10 had the biggest group size and biggest contribution to cesarean rates followed by group 5. Conclusion: Tertiary care government hospitals have a higher cesarean rates due to referral of high-risk pregnancies. Increasing the rates of trial of labour after caesarean is one of the interventions that may serve to decrease the caesarean rates in such institutions.